Tanycyte-derived lactate activates astrocytic HCAR1 to modulate glutamatergic signaling and POMC neuron excitability - Sergio López; Roberto Elizondo-Vega; Vinka Azócar; Vania Sepúlveda; Valentina Opazo-Mellado; Walter Vásquez; Juan C. Sáez; Ricardo C. Araneda; María de los Ángeles García-Robles (Proceedings of the National Academy of Sciences, 2026)
Astrocytes and tanycytes play essential roles in hypothalamic metabolic sensing, yet how glial–glial communication translates metabolic cues into neuronal activity remains poorly understood. We previously demonstrated that tanycytes release lactate and that this metabolite modulates the activity of arcuate pro-opiomelanocortin (POMC) neurons. Here, we identify the lactate receptor, HCAR1, as a key mediator of tanycytes-astrocyte-neuron signaling in the arcuate nucleus. We show that HCAR1 is highly expressed in hypothalamic astrocytes and present in a subset of NPY neurons. In primary hypothalamic cultures, L-lactate, the endogenous agonist of HCAR1, elicited increases in astrocytic cytosolic Ca 2+ and stimulated glutamate release; both effects were abolished by HCAR1 silencing using siRNA. In parallel, L-lactate and 3Cl-HBA increased connexin hemichannel activity, and hemichannel inhibition reduced glutamate release. Consistent with these in vitro observations, focal intracellular glucose delivery to a single tanycyte in acute hypothalamic slices triggered rapid Ca 2+ elevations in neighboring astrocytes, revealing functional glial–glial communication in situ. Importantly, activation of astrocytic HCAR1 enhanced NMDA receptor-dependent slow inward currents and excitability in POMC neurons, an effect reproduced by pharmacological HCAR1 agonists and abolished by astrocytic HCAR1 silencing. Together, these findings uncover a glial metabolic relay in which tanycyte-derived lactate activates astrocytic HCAR1, promotes glutamate release, and enhances POMC neuron excitability, providing a mechanistic link between cerebrospinal fluid-borne glucose fluctuations and hypothalamic control of feeding.